DEIXIS ANALYSIS IN MOVIE SCRIPT OF “ENCANTO” : Pragmatics, Discourse Deixis, Social Deixis, Movie Script, Encanto - Ika Trisnantasari (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
This study aims to explain the meaning of discourse deixis and social deixis found in the movie script of Encanto, and describe the role of context in determining the references of each deixis that is found in the movie. In this research, the researcher used descriptive qualitative method. After finding the movie script, the researcher marked the discourse deixis and social deixis to be analyzed using the theory of Levinson. The result of this research shows that there are 20 data of discourse deixis and 15 data of social deixis. Generally, the discourse deixis refer to other expression mention in some part of the discourse. The social deixis in this research shows the social status among the speakers. The social status of the other speakers depends on the context when the conversation happens. The referents of both discourse deixis and social deixis are determined by the context where they are used.